Outcomes of Negotiation on Halal Meat Business - Norhayati Rafida Abdul Rahim; Mohd Nazmi Abd Manap; Alina Abdul Rahim; Balqish Juliana Ali; Mohd Hazim Bin Mohd Yusop; Syamsul Kamar Wahab @ Muhamad; Musa Ahmad; Sukri Hassan (Universiti Sains Islam Malaysia, 2024)
Indexed by Scopus